Usage of calcium carbonate biodeposition in modification of cementitious composites - Zawal, Daniel; Dobosz, Agnieszka; Górski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Biodeterioration of construction materials is an undesired phenomenon, generating high costs of constraction repairs. On the other hand, occurrence of some bacteria can affect prevention and self repair of fractures formed in concrete. Biodeposition is an effective solution for increasing compressive strength of concrete, extending durability of concrete constructions and renovating limestone elements in facades of historic buildings.
Keywords: biodeposition of calcium carbonate; ureolisis; self-healing of concrete